Theories of the policy process - Weible, Christopher M. (Routledge, Taylor & Francis Group, 2023)
"Theories of the Policy Process provides a forum for the experts in policy process research to present the basic propositions, empirical evidence, latest updates, and the promising future research opportunities of each policy process theory. In this thoroughly revised fifth edition, each chapter has been updated to reflect recent empirical work, innovative theorizing, and a world facing challenges of historic proportions with climate change, social and political inequities, and pandemics, among recent events. Updated and revised chapters include Punctuated Equilibrium Theory, Multiple Streams Framework, Policy Feedback Theory, Advocacy Coalition Framework, Narrative Policy Framework, Institutional and Analysis and Development Framework, and Diffusion and Innovation. This fifth edition includes an entirely new chapter on the Ecology of Games Framework. New authors have been added to most chapters to diversify perspectives and make this latest edition the most internationalized yet. Across the chapters, revisions have clarified concepts and theoretical arguments, expanded and extended the theories' scope, summarized lessons learned and knowledge gained, and addressed the relevancy of policy process theories. Theories of the Policy Process has been, and remains, the quintessential gateway to the field of policy process research for students, scholars, and practitioners. It's ideal for those enrolled in policy process courses at the undergraduate and graduate levels, and those conducting research or undertaking practice in the subject"--